A Comparative Study on the Efficacy of Chitosan Gel Formulation and Conventional Silver Sulfadiazine Treatment in Healing Burn Wound Injury at Molecular Level - Kumar, Dr. Amit (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: Comparison of the efficacy of a novel 5% chitosan gel formulation in healing burn wound with respect to conventional silver sulfadiazine (SSD) treatment at molecular level. Materials and Methods: Different concentrations of chitosan gel were formulated and optimized with respect to spreadability, extrudability, and viscosity. Burn wounds were created on 18 rats with three groups of six animals each. Group I served as control, Group II animals were treated with standard SSD ointment, and Group III animals were treated with optimized chitosan gel till 16 days. Wound healing efficacy was compared by calculating the percentage of wound contraction, and any difference in wound healing property at the molecular level was ascertained by the levels of hydroxyproline, hexosamine, collagen, and antioxidant analysis. Results: On the basis of viscosity, spreadability and extrudability, 5% chitosan gel was selected as the optimized test formulation. Group III animals treated with chitosan gel showed faster contraction in wound area in comparison with control and standard treatment groups. At the end of 16th day, 95.5 ± 2.4%, 84.14 ± 2.1%, and 34.9 ± 2.1% healing was observed in case of chitosan gel, standard, and control treatments, respectively. Topical application of 5% chitosan gel increased collagen synthesis and stabilization at the wound site, as evidenced by increase in hydroxyproline and hexosamine levels, and up-regulated expression of collagen Type I. Furthermore, there was a significant increase in levels of endogenous enzymatic and nonenzymatic antioxidants and decrease in lipid peroxide levels in chitosan gel treated burn wound granulation tissue. Histological examination also confirmed the better healing efficacy of 5% chitosan gel in comparison to standard treatment. Conclusion: Results indicate that 5% chitosan gel has the potential to be developed as an effective burn wound healing agent in comparison to existing treatment option.